El refuerzo académico en educación básica superior en el área de matemática - Palomo Semblantes, Juan Carlos (2017)
The present investigation is directed to be a diagnosis of the problematic observed in the Leopoldo N. Chávez Educational Unit of the community center of the Guangaje parish Pujilí Canton, Cotopaxi Province. Under this perspective, it has been proposed to investigate the effects of Academic Reinforcement in the area of Math. Treating it as an educational problem which affects to the students of this institution has seen the feasibility of doing so, the research is based on a general objective and three specific ones that guided the progress of the process. In the same way we inquire scientific information in sources wich give veracity from this perspective. Data and information of the students and the responsible teacher have been collected, using research instruments such as the survey and the interview, which has provided first-hand information and from the place of events and with the actors of the educational process. The information collected has been processed according to methods such as statistics and analysis has also allowed us to sustain the problem and confront the reality of the institution. The data are analyzed and we have given our interpretation of each of the questions, as well as the criteria issued by the teacher who teaches the Math Area. All the work carried out allowed us to issue conclusions and recommendations that will serve as a basis for future research. Also a point to highlight are the impacts that this may have in the fields such as social, educational and pedagogical, which we are sure will serve to better visualize the educational aspect especially in relation to the Academic Reinforcement in the different areas its effects on the teaching-learning process and school performance of young students.